Identification of key macrophage-related genes in systemic sclerosis–associated interstitial lung disease based on single-cell and bulk transcriptomic data - Ting Zhao; Yulin Wang; Fu-an Lin (PLoS ONE, 2026)
Background Systemic sclerosis–associated interstitial lung disease (SSc-ILD) is a major clinical challenge with no effective treatments. It is also the leading cause of death in patients with systemic sclerosis. Thus, understanding its underlying molecular mechanisms, particularly those related to macrophage-related gene functions, is critical to address this urgent medical need. Methods In this study, single-cell and transcriptomic data retrieved from a public database were analyzed to investigate the underlying molecular mechanisms of SSc-ILD. A series of comprehensive analyses was conducted, including cell–cell communication analysis, pseudotime trajectory analysis, and high-dimensional weighted gene co-expression network analysis, to identify pertinent genes linked to macrophage modules. Candidate genes were determined by intersecting differentially expressed genes (DEGs) with macrophage module genes. Subsequently, key genes were identified through protein–protein interaction (PPI) network analysis and gene expression validation. Various analytical procedures were used to evaluate the function of the key genes in the regulatory roles of SSc-ILD, including enrichment analysis, immune infiltration analysis, drug prediction, and molecular docking. Results Of the 1515 DEGs and 400 macrophage module genes intersected, 50 candidate genes were identified. In particular, ARG2 , ELF3 , and NKX2–1 emerged as key genes through subsequent PPI network analyses and gene expression evaluations. Enrichment analyses revealed a notable co-enrichment of the lysosomal pathway with these key genes. Moreover, immune infiltration analysis revealed a strong negative correlation between NKX2–1 and monocytes, whereas ELF3 and ARG2 exhibited a positive association with activated dendritic cells. The molecular docking results showed that the binding energies of ARG2-SKA-111/cyclophosphamide and ELF3–voruciclib/cyclophosphamide were less than − 5 kcal/mol. Conclusion The findings of this study highlight the key roles of ARG2, ELF3, and NKX2−1 in macrophage-related mechanisms of SSc-ILD, providing insights into potential therapeutic targets. Further research is necessary to explore their functional implications in disease progression and treatment.